Thermodynamic and Kinetic Analysis for Transformation of Oxide Inclusions in Solid 304 Stainless Steels. Issue 7 (27th February 2019) - Wang, Jujin; Li, Weifu; Ren, Ying; Zhang, Lifeng
Abstract : Inclusions in 304 stainless steels are transformed from manganese silicate to manganese chromite (spinel) upon heating in the range of 1000–1350 °C, while this transformation is not observed when heating temperature is 1400 °C. Thermodynamic analysis with software FactSage™ is applied in interpreting the transformation. Manganese chromite spinel, with light color under SEM, is deemed to be formed on the surface of MnO–SiO2 inclusions by the reaction between Cr in steel matrix and MnO–SiO2 in inclusions. Heating experiments with different time at 1235 °C (rolling insulation temperature) are carried out to confirm the kinetics of the transformation reaction. Mass transfer coefficients of inclusions' composition, SiO2, MnO, and Cr2 O3 are ranging from 5 × 10 −7 to 9 × 10 −7 m s −1, depending on diameters and components of inclusions. Abstract : Inclusions in 304 stainless steels are transformed form manganese silicate to manganese chromite upon heat treatment at rolling insulation temperature (1235 °C). The transformation is a diffusion‐control process, and shows strong effects of heating time. The mass transfer coefficients of oxides in inclusions are calculated through the change of concentration with time.